A mixed-method evaluation of peer-education workshops for school-aged children to teach about antibiotics, microbes and hygiene. (18th March 2017) - Young, Vicki L.; Cole, Amy; Lecky, Donna M.; Fettis, Dennis; Pritchard, Beth; Verlander, Neville Q.; Eley, Charlotte V.; McNulty, Cliodna A. M.
Abstract: Background: Delivering health topics in schools through peer education is known to be beneficial for all students involved. In this study, we have evaluated a peer-education workshop that aims to educate primary and secondary school students on hygiene, the spread of infection and antibiotics. Methods: Four schools in south-west England, in a range of localities, took part in peer-education workshops, with students completing before, after and knowledge-retention questionnaires. Mixed-effect logistic regression and mixed-effect linear regression were used to analyse the data. Data were analysed by topic, region and peer/non-peer-educator status. Qualitative interviews and focus groups with students and educators were conducted to assess changes in participants' skills, confidence and behaviour. Results: Qualitative data indicated improvements in peer-educator skills and behaviour, including confidence, team-working and communication. There was a significant improvement in knowledge for all topics covered in the intervention, although this varied by region. In the antibiotics topic, peer-educators' knowledge increased in the retention questionnaire, whereas non-peer-educators' knowledge decreased. Knowledge declined in the retention questionnaires for the other topics, although this was mostly not significant. Conclusions: This study indicates that peer education is an effective way to educate young people on important topics around health and hygiene, and to concurrently improve communication skills. Its use should be encouraged across schools to help in the implementation of the National Institute for Health and Care Excellence (NICE) guidance that recommends children are taught in an age-appropriate manner about hygiene and antibiotics.